Factores que influyen en el E-loyalty de los negocios "Pure Play" - Alcoser Kok, Sebastian Stefano (2023)
Currently, consumers have a wide range of platforms to buy online, which is why it is increasingly difficult for companies to achieve customer loyalty. Different authors have carried out many studies over the years about loyalty, which today has evolved into the concept of digital loyalty. The Peruvian digital consumer has increased considerably in recent years, being boosted as a result of the pandemic caused by Covid 19. However, little research has been identified on e-loyalty and the model of pure plays retail in Peru. This research seeks to confirm the findings that have been obtained internationally about the factors that affect digital loyalty, focusing on the current Peruvian market and serving as a basis for the discovery of future findings that take the subject in greater depth.